2018
DOI: 10.1007/s00198-018-4553-2
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of osteoporosis treatment after hospitalization for hip fracture in Hawaii

Abstract: The use of osteoporosis medication for secondary prevention after admission for hip fracture in Hawaii is low. Efforts need to be made to improve treatment rates, especially among males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…The results of our analysis are in line with other studies on secondary fracture prevention, which have demonstrated significant treatment gaps across healthcare systems and settings [ 19 26 , 28 , 30 ]. While many such studies are based in North America [ 19 22 , 25 , 26 , 28 ], our study along with several others demonstrate that the treatment gap seems to be a universal problem [ 23 , 24 , 30 ], also pertaining to European healthcare systems with a high level of access. Previous longitudinal studies have demonstrated an increasing treatment gap over time [ 25 , 26 ], and while our study provides more recent data with significant differences between the UK, Catalonia, and Denmark, the overall impression is that the gap is stable or increasing in recent years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of our analysis are in line with other studies on secondary fracture prevention, which have demonstrated significant treatment gaps across healthcare systems and settings [ 19 26 , 28 , 30 ]. While many such studies are based in North America [ 19 22 , 25 , 26 , 28 ], our study along with several others demonstrate that the treatment gap seems to be a universal problem [ 23 , 24 , 30 ], also pertaining to European healthcare systems with a high level of access. Previous longitudinal studies have demonstrated an increasing treatment gap over time [ 25 , 26 ], and while our study provides more recent data with significant differences between the UK, Catalonia, and Denmark, the overall impression is that the gap is stable or increasing in recent years.…”
Section: Discussionsupporting
confidence: 89%
“…Despite such evidence-based recommendations, a significant post-fracture treatment gap is known to prevail across healthcare systems and settings [19][20][21][22][23][24][25][26][27][28]. Several publications report that in some countries as few as 10-20% of patients with fragility fractures go on to receive AOM [23][24][25][26][27], with this gap being more pronounced in men as well as in the elderly [20,26,29].…”
Section: Introductionmentioning
confidence: 99%
“…Our study is limited to a single large health care system in Hawai‘i. Therefore our findings may not be generalizable to other health care systems [33]. Nevertheless, it does complement prior studies about suboptimal gout care, and as previously mentioned provides important information about gout care in Hawai‘i.…”
Section: Discussionmentioning
confidence: 45%
“…The DEXA scanning rates in previous studies ranged from 1.4% in a retrospective cohort study by Barton et al [13] to 32.0% in Hawaii in a study by Nguyen et al [14] and to 52.9% in South Korea in a study by Park et al [15], which differ from the results of our study, as most of the physicians in our study agreed to performing DEXA bone mineral density (BMD) scan to middle-aged and elderly patients with suspected OVCF. The results of previous studies and our results suggest that the rate of BMD measurement has increased over the years; however, doctors' knowledge and attitude may not translate into action in diagnosis.…”
Section: Discussionmentioning
confidence: 94%